Rough Creek - Warner, Kaki (Warner, Kaki. Brides of Rough Creek Texas novel, 2020)
"After serving eighteen months in prison for a crime he didn't commit, Dalton Cardwell is looking for a fresh start. What better place than Whitcomb Four Star Ranch? He doesn't regret the decisions of his past, he'd choose the same roads again. But now all Dalton wants is to keep his head down and focus on the horses and on Raney Whitcomb. Raney is outraged when she learns her mother hired an ex-con. Raney has worked hard for the ranch, sacrificing her personal life for the dream of building on her family's legacy. But as Dalton breaks down every misconception and even wins the good opinion of her sisters, Raney is forced to rethink her stance and finally free herself to explore the heart-pounding tension that simmers between them."--Provided by publisher.